Peran Kearifan Lokal dalam Meningkatkan Pemahaman Geografi dan Sejarah dalam Pembelajaran IPS: Studi Literatur di Gresik dan Lamongan - Octavian Hendra P; Ilham Galih Pambudi (PT. Hasba Edukasi Mandiri, 2025)
This study examines the role of local wisdom in enhancing the understanding of geography and history concepts in social studies (IPS) education in Gresik and Lamongan. Through a literature review, it was found that local wisdom, such as traditional navigation systems, shipbuilding techniques, and environmental conservation practices, can serve as effective contextual learning resources. The findings indicate that integrating local wisdom improves students' comprehension, spatial thinking skills, and cultural awareness. However, the implementation of this model faces challenges, including a lack of systematic documentation and limited teacher competence. Therefore, training for educators and collaboration with local communities are necessary. This study recommends the development of a flexible curriculum and the utilization of digital technology to enrich learning experiences. With this approach, social studies education is expected to become more contextual, relevant, and meaningful for students.